0990 Moderated Mediation Effect Of Sleep Disturbance In The Relationship Between Non-suicidal Self-injury And Suicidality In Female University Students. (27th April 2018) - Park, K; Lee, J; Hagan, C; Joiner, T; Suh, S
Abstract: Introduction: Non-suicidal self-injury(NSSI) and suicidality co-occur frequently, and sleep disturbances are considered a risk factor for both behaviors. The interpersonal theory of suicide indicates that NSSI increases the threshold of pain tolerance, and subsequently increases one's capacity for suicide. Previous studies have suggested that the mechanism between NSSI and suicidal ideation is mediated by interpersonal needs, namely thwarted belongingness and perceived burdensomeness. The purpose of the study is to investigate the moderated mediation effect of sleep disturbance in the relationship between NSSI and suicidal ideation in female university students. Methods: This sample consisted of 291 undergraduate female students (mean age 21.17 ± 1.74). All participants completed questionnaires about non-suicidal self-injury (Self-injurious thoughts and behaviors interview; SITBI), thwarted belongingness and perceived burdensomeness (Interpersonal Needs Questionnaire; INQ), suicidal ideation (Depressive Symptoms Inventory; DSI) and 7-day sleep diaries. Moderated mediation analyses were conducted to investigate sleep disturbance (measured by wake after sleep onset; WASO) as a moderator for the mediators thwarted belongingness and perceived burdensomeness, in the relationship between NSSI and suicidal ideation. Results: Mediation analysis revealed that perceived burdensomeness and thwarted belongingness partially mediated the relationship between NSSI and suicidal ideation. WASO moderated the relationship between NSSI and perceived burdensomeness (B=.0609, SE=.0192, p<.01, 95% CI [.0230, .0987]), but not the relationship between NSSI and thwarted belongingness. The indirect effect of perceived burdensomeness on the relationship between NSSI and suicidal ideation was significant for those who experience increased WASO (B=.3373, SE=.1366, 95% CI [.2993, .8767]). The indirect effect was not significant for who report low WASO (B=.2303, SE=.1239, 95% CI [-.0132, .4776]). Conclusion: These findings highlight that individuals who report NSSI and increased WASO have higher perceived burdensomeness compared to those who report low WASO, which subsequently leads to suicidal ideation. Support (If Any):